The IDEFICS Intervention Toolbox - A Guide to Successful Obesity Prevention at Community Level - Verbestel, Vera; Henauw, Stefaan De; Marild, Staffan; Bonsmann, Stefan Storcksdieck genannt; Celemín, Laura Fernández; Gallois, Katharina; Hassel, Holger; Bourdeaudhuij, Ilse De (IntechOpen, 2012)
None